Penyuluhan Digital Marketing Pada Usaha Kecil dan Menengah di Kelurahan Cipondoh Makmur, Kecamatan Cipondoh, Kota Tangerang - Wendi Usino; Dewi Murtiningsih; Feby Lukito Wibowo (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
The use of digital technology-based marketing concepts is a hope for small and medium-sized businesses to develop to be very important. Small and Medium Enterprises can use social media as a means of digital marketing. In addition to low costs, social media is considered capable of directly reaching consumers. Digital marketing is a means to introduce products through digital media. The development of the digital world is currently a trend and a necessity in all circles. The number of SMEs that are still experiencing difficulties in the product marketing process is an obstacle in business development. The purpose of this activity is to increase the capabilities of small and medium-sized enterprises through digital marketing to market a wider range of products so that sales can increase; the ability of small and medium-sized businesses to develop through digital marketing; Get to know more about Budi Luhur University with the residents of Budi Luhur University.